Teachers’ Challenges in Teaching English to Students with Special Needs - Musthafa, Fahmi; Hendi Pratama; Katharina Rustipa (English Education Journal, 2024)
This study investigates the challenges faced by teachers in teaching English to students with special needs, using a descriptive case study design. Two teachers of a special school participated by sharing their teaching experiences through questionnaires and structured interviews to provide detailed insights. There were six steps of data analysis, including extensive transcription review, generation of initial codes, theme identification, theme analysis, theme definition and naming, and report creation. Three key research topics emerged, highlighting the persistent difficulties special education teachers face. The findings show that English teachers faced some challenges, including a lack of awareness, a lack of teaching materials, a lack of special needs teachers, and a poor teaching environment. It indicates that teachers require professional training to enhance their teaching effectiveness and must take the initiative in self-educating about special education. Teachers are also expected to have high initiative to educate themselves about special education and continue to strive to apply effective teaching methods. The government is also responsible for supporting adequate teaching facilities and preparing the best teachers, such as providing professional training for teachers who teach in special schools.